The situation of lyrical literature in the sixth century - Asadi, Mostafa (2021)
The sixth century is the Seljuk period from exciting times to different centuries in Iran. This study analyzes the causes and factors of changes in the style of poetry and its content and themes and changes the sponsors of poetry and finding poetry among the common people Mysticism and Sufism have dealt with the needs of the troubled society of that century.  In this study, due to the tendency of the monasteries towards the monasteries in the sixth century and the lack of attention of the Seljuk kings to the poets, there was a lack of introspection of the poet and interesting mystical agreements in his view and attention.